Integration of Digital Pedagogy in ELT: Teacher Perception on Learning Achievement and Professional Development - Kadel, Purna Bahadur; Tiwari, Hari Prasad (Tribhuvan University Journal, 2025)
Implementation of digital pedagogy in English language teaching is essential to enhance the language skills, vocabulary, and grammatical competence of the learners and professional development of ELT teachers at school level. This study would be very relevant to address issues of Information and Communication Technology (ICT) of learners and teachers at secondary school level in Nepal. The purposes of this study were to find out the perceptions of English teachers of community and institution schools regarding the use of digital pedagogy to develop learning achievement of learners and teacher professional development and investigate the impact of digital pedagogy on teachers and learners. We employed hermeneutic phenomenological research design to accomplish this study in which lived experiences of English teachers were collected using in-depth semi structured interview. Eight English teachers particularly, 4 from community and 4 from institutional schools were selected as a sample for this study from Kathmandu metropolitan city. The findings of this study revealed enhancement of learning achievement through classroom engagements, enriching teacher professional development, developing of critical thinking and creative skills of learners through ICT, improving English language competency of learners through digital pedagogy, and developing 21st century skills through ICT through the integration of digital pedagogy in English language Teaching at school level. The digitalization of English language teaching and learning at school level is essential for the learners and teachers to be adapted and accommodated them in this globalized global village.